Identifikasi Hama dan Penyakit Pada Tanaman Anggrek Bulan (Phalaenopsis amabilis) - Ari Monawati; Desi Rhomadhoni; Nur Rokhimah Hanik (Florea : Jurnal Biologi dan Pembelajarannya, 2021)
Orchid is the general name for all types of plants in the family Orchidaceae (family of orchids). This family is one of the largest groups among other flowering plants. It is estimated that worldwide there are around 15,000-20,000 species of orchids with 900 genera (clans) that grow endemic to forests scattered in various countries. Of all orchid species in the world, 5,000 of them are in Indonesia. Broadly speaking, the classification of orchids is divided into 5 subfamilies, 16 tribes (tribes), and 28 subtribes. Phalaenopsis is a genus of orchids which is popular for its diversity and beauty of flowers. The government through presidential decree (Kepres) No. 4 of 1993, on January 9, 1993, designated the moon orchid as a charm flower named Latin Phaleonopsis amabilis, this orchid grows attached to a tree trunk or branch and is one type of orchid endemic to Indonesia. The development of orchid cultivation has never been separated from disease and pest problems. With few disease infections and pest attacks, the beauty will change, of course, the selling price will fall. Orchid plants require extra care to grow with beautiful flowers. Orchid disease can be caused by bacteria, fungi or viruses. Diseases and pests that attack orchid plants can cause death if allowed to continue. Besides that, mishandling can also cause the death of orchids. The purpose of this study was to determine the pests and diseases of the Phalaenopsis amabilis plant.This research was conducted on December 2, 2020 and January 13-14, 2021 in Carikan Sukoharjo with 10 samples of Phalaenopsis amabilis plants. The tools needed in this research include writing tools, tables, loops and documentation tools (cellphone cameras). The variables to be observed were diseases and pests that attacked. The methods used were direct observation and interviews, the data obtained were analyzed by qualitative descriptive.Research conducted on 10 samples of Phalaenopsis amablis, found 6 pests and 2 diseases. Pests on the Phalaenopsis amabilis Moon Orchid plant are found that very often attack such as ants, snails, grasshoppers, mealybugs, mites and caterpillars. Whereas in the disease of the Moon Orchid plant (Phalaenopsis amabilis) in the search for Sukoharjo, the fungus Fussarium oxyporum and Rhizoctonia solani attack the leaves, stems, roots of Phalaenopsis amabilis. This disease enters the plant tissue through stomata or wounds in plants. In general, the characteristics of a fungal attack include small spots on the leaves, blisters like being scalded, watery, either cloudy or clear.